2012
DOI: 10.5194/se-3-265-2012
|View full text |Cite
|
Sign up to set email alerts
|

Plate kinematics in the Cantabrian domain of the Pyrenean orogen

Abstract: The Cantabrian domain represents the western portion of the Pyrenean orogen, in the area where the Iberian continental lithosphere was subducted toward the north underneath the transitional to oceanic lithosphere of the Bay of Biscay. There, the about 100 km of orogenic convergence have been mostly accommodated in the northern portion of the orogen (i.e. the retro wedge) developed in the Bay of Biscay abyssal plain, while only crustal-scale folding with limited internal deformation occurred in the Cantabrian s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 66 publications
4
49
0
Order By: Relevance
“…As such, they are capable of nucleating large earthquakes as a result of late Quaternary extensional reactivation. With this respect, the soft-linked, "immature" fault system mapped in the study area probably results not only from the young age of postorogenic extension, but also from the decoupling effect (e.g., Vendeville et al, 1987;Allemand and Brun, 1991;Richard and Krantz, 1991;Tavani, 2012) of the ductile level separating the shallow allochthonous multilayer from the deeper Apulian Platform carbonates and faulted basement.…”
Section: Tectonic Modelmentioning
confidence: 98%
“…As such, they are capable of nucleating large earthquakes as a result of late Quaternary extensional reactivation. With this respect, the soft-linked, "immature" fault system mapped in the study area probably results not only from the young age of postorogenic extension, but also from the decoupling effect (e.g., Vendeville et al, 1987;Allemand and Brun, 1991;Richard and Krantz, 1991;Tavani, 2012) of the ductile level separating the shallow allochthonous multilayer from the deeper Apulian Platform carbonates and faulted basement.…”
Section: Tectonic Modelmentioning
confidence: 98%
“…ACCEPTED MANUSCRIPT 22 and Brun, 1991;Richard and Krantz, 1991;Tavani, 2012;Vendeville et al, 1987) of the thick ductile zone separating the shallow rigid lid from the faulted buried Apulian Platform carbonates and underlying basement. It is worth noting that the interpretation proposed in this paper is not in contrast with that implying an interaction between the Alta Val d'Agri best fitting all available constraints (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A major break occurred in Aptian time [ Olivet , ] as a result of the counterclockwise rotation of Iberia [ Gong et al , ; Jammes et al , , ]. As a consequence of this rotation, a NNE‐SSW to NE‐SW extension is initiated in rift basins preserved onshore [ Jammes et al , ; Lagabrielle et al , ; Roca et al , ; Tavani , ] as emphasized by the NE‐SW segmentation observed (e.g., Pamplona, Toulouse, and Cevennes faults). These NE‐SW transfer faults cross the Iberian‐European plate boundary and are locally sealed by Albian sediments (Pamplona fault, between the Basque‐Cantabrian and Arzacq‐Mauléon basins [ Razin , ; Claude , ]).…”
Section: Geological Frameworkmentioning
confidence: 99%